Histone Posttranslational Modifications in Breast Cancer and Their Use in Clinical Diagnosis and Prognosis - Magnani,L; Louloupi,A; Zwart,W (2016)
Epigenetic regulation plays a key role in normal physiology and disease. In breast cancer, multiple epigenetic regulators have been found to be causally involved in tumorigenesis and treatment resistance. Since treatment resistance in breast cancer is commonly observed, epigenetic modifiers may represent promising targets for pharmaceutical intervention. Multiple epigenetic modifiers are currently being targeted in clinical trials with varying success rates. Yet, biological roles of epigenetic modifiers are complex and lack tissue specificity, which may diminish any therapeutic window. Is epigenetic profiling the "new black" of biomarker discovery in breast cancer? and would epigenetic drugs yield the new "silver bullet" in breast cancer treatment, or are we dealing with a "red herring"?